Characterization of Movable Fluid Distribution in Tight Oil Reservoirs by NMR and Centrifugation. (9th February 2023) - Wang, Tong; Zhang, Dongdong; Wang, Xin; Wang, Zhangchao; Zhang, Wen; Sun, Wenyi; Ma, Mingyang
Abstract : The reservoir of Chang 7 Member of Yanchang Formation in the Ordos Basin is rich in tight oil resources, with well-developed micro-nanopore throats, strong heterogeneity, and complex fluid distribution characteristics. In this paper, a combination of nuclear magnetic resonance and centrifugation experiments is carried out to qualitatively and quantitatively analyze and evaluate the distribution characteristics of the movable fluid in Chang 7 reservoirs in Baibao Block. With different centrifugal forces, the NMR T2 spectrum characteristics of saturated water state and different centrifugal force state can be obtained, and the movable fluid distribution characteristics under the control of different centrifugal forces and different pore throat intervals can be obtained. The research results demonstrate that the NMR T2 spectrum of the Chang 7 tight oil reservoir in the study area presents a double-peak or triple-peak shape. With the increase of centrifugal force, the water saturation value of the corresponding sample gradually decreases. The overall movable fluid saturation ranged from 19.07% to 32.52%, with an average of 26.23% and a low degree of movability. The submicron (0.1 1 μ m) and nanoscale (0.075 0.1 μ m) pore throats were the main pore throat intervals controlling the movable fluid saturation of the studied samples, accounting for an average of 18.31% and 5.57%, respectively, and micron-scale pore throats (r > 1 μ m ) accounted for an average of 2.35% of the movable fluid distribution.